The Effect Of Work Discipline And Employee Competence On Civil Servant Performance With Employee Motivation As An Intervening Variable At The Regional Secretariat Of Cilegon City - Fadhil Rahmat Fauzi; Muhammad Suparmoko; Wahyu Wiguna (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
This study addresses the declining performance of Civil Servants at the Regional Secretariat of Cilegon City, which is associated with low work motivation, inadequate discipline, and insufficient employee competence. These issues are reflected in the failure to achieve performance targets optimally, limited employee initiative, and recurring disciplinary violations. The study aims to examine the influence of work discipline and employee competence on employee performance, with work motivation acting as an intervening variable. A quantitative survey approach was employed involving 107 Civil Servants as respondents. Data were collected through questionnaires and analysed using Partial Least Square-Structural Equation Modelling (PLS-SEM). The findings indicate that both work discipline and employee competence have a positive and significant effect on employee performance. In addition, work motivation strengthens the relationship between employee competence and performance, although it does not fully mediate the effect of work discipline on performance. These results emphasize the important role of motivation in improving employee performance through enhanced competence. Therefore, the Cilegon City Government is encouraged to strengthen discipline enforcement, expand competency development programs, and implement sustainable motivational strategies. Such efforts are expected to create a workforce that is disciplined, competent, and motivated, ultimately supporting the achievement of organizational goals and improving public service performance.